SIMULASI PENGENDALI SUHU DAN KELEMBABAN PADA BUDIDAYA JAMUR TIRAM DENGAN METODE FUZZY LOGIC SUGENO: PENDEKATAN KONSEPTUAL - Blegur, Ernes Josias; Bonnu, Christin Hendriyani (Politeknik Bisnis Indonesia, 2025)
Oyster mushroom (Pleurotus ostreatus) cultivation requires ideal environmental conditions, particularly temperature and humidity parameters, to achieve optimal growth. This study aims to evaluate the effectiveness of applying fuzzy logic through the Sugeno method in developing an automatic control system for oyster mushroom cultivation, with the study limited to the system simulation stage. The simulation results show that the Sugeno method is capable of producing high accuracy in the decision-making process and adaptive adjustment of environmental parameters. The developed system is able to maintain the average value of air humidity in the range of 80–90% and air temperature between 22–28°C, in accordance with the ideal conditions for oyster mushroom growth. This research can be a foundation for further development in the implementation of efficient and sustainable control systems, especially in supporting oyster mushroom farmers in the North Central Timor region.